Copper Sulfide Nanocrystal Level Structure and Electrochemical Functionality towards Sensing Applications. Issue 5 (19th November 2015) - Vinokurov, Kathy; Elimelech, Orian; Millo, Oded; Banin, Uri
Abstract: The level structure of copper sulfide nanocrystals of different sizes was investigated by correlating scanning tunneling spectroscopy and cyclic voltammetry data in relation to sensing applications. Upon oxidation of Cu2 S nanocrystals in the low‐chalcocite phase, correlated changes are detected by both methods. The cyclic voltammetry oxidation peak of Cu(1+) down shifts, while in‐gap states, adjacent to the valence‐band edge, appeared in the tunneling spectra. These changes are attributed to Cu vacancy formation leading to a Cu depleted phase of the nanocrystals. The relevance of the oxidation to the use of copper sulfide nanocrystals in hydrogen peroxide sensing was also addressed, showing that upon oxidation the sensitivity vanishes. These findings bare significance to the use of copper sulfide nanocrystals in glucose sensing applications. Abstract : The level structure of Cu2 S and oxidized Cu2− x S nanocrystals of different sizes is investigated by correlating scanning tunneling spectroscopy and cyclic voltammetry. The electrochemical sensitivity towards H2 O2 reduction is affected by the copper sulfide stoichiometric phase, which is an important parameter for biocompatible electro‐systems.